Tire wear mechanisms and how they relate to wear particle sizes – a brief review - Alexander Schmiedhofer; Pierluigi Bilotto; Carsten Gachot (Industrial Lubrication and Tribology, 2026)
Purpose The new EURO 7 regulation will set limits on non-exhaust emissions, which include tire wear. Therefore, this study aims to develop a comprehensive understanding of how tire wear particles are formed, their size distribution, and the influence of factors such as vehicle weight, speed, and road surface conditions. Design/methodology/approach Tire wear is caused by three different mechanisms: Cut and chip (abrasion), fatigue, and chemical wear. Each mechanism appears differently, thus each of them is described separately in a respective chapter. Findings All three wear mechanisms can occur at all times, but, depending on the tearing energy, one is usually dominant: Cut and chip happen at high energy levels, fatigue at medium energy levels, and chemical wear at low energy levels. Each mechanism produces different particle sizes, from the mm to the nm range, but most commonly in the range of 2.5 µm–10 µm. Originality/value A lot of research has been done on tire and rubber wear, but the size of wear debris particles was often an afterthought, therefore, this work summarizes all available information on this topic. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-08-2025-0372/